Recent Advances in Design Strategies for Tough and Stretchable Hydrogels - Maiti, Chiranjit; Imani, Kusuma Betha Cahaya; Yoon, Jinhwan (ChemPlusChem (Weinheim, Germany), 2021)
The development of multifunctional hydrogels with excellent stretchability and toughness is one of the most fascinating subjects in soft matter research. Numerous research efforts have focused on the design of new hydrogel systems with superior mechanical properties because of their potential applications in diverse fields. In this Minireview, we consider the most up‐to‐date mechanically strong hydrogels and summarize their design strategies based on the formation of double networks and dual physical crosslinking. Based on the synthetic approaches and different toughening mechanisms, double‐network hydrogels can be further classified into three different categories, namely chemically crosslinked, hybrid physically–chemically crosslinked, and fully physically crosslinked. In addition to the above‐mentioned methods, we also discuss few uniquely designed hydrogels with the intention of guiding the future development of these fascinating materials for superior mechanical performance. Tough stuff: This Minireview highlights network designs to prepare mechanically tough and stretchable hydrogels. These design strategies are generally focused on the formation of double networks and dual physical crosslinking of various polymeric materials. Double networks can be further detailed into chemically crosslinked, fully physical crosslinked, and hybrid chemically‐physically crosslinked.